1999
DOI: 10.1121/1.428053
|View full text |Cite
|
Sign up to set email alerts
|

On the lingual organization of the German vowel system

Abstract: A hybrid PARAFAC and principal-component model of tongue configuration in vowel production is presented, using a corpus of German vowels in multiple consonant contexts (fleshpoint data for seven speakers at two speech rates from electromagnetic articulography). The PARAFAC approach is attractive for explicitly separating speaker-independent and speaker-dependent effects within a parsimonious linear model. However, it proved impossible to derive a PARAFAC solution of the complete dataset (estimated to require t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 14 publications
5
50
0
Order By: Relevance
“…The tongue has been frequently characterized as being composed of several functionally independent articulators ͑Hardcastle, 1976; Hoole, 1999;Mermelstein, 1973;Ö hman, 1967;Perkell, 1969;Stone, 1990͒. The common use of such terms as tip, blade, body, dorsum, and root to refer to the ''parts'' of the tongue reflects the widespread acceptance of this assertion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tongue has been frequently characterized as being composed of several functionally independent articulators ͑Hardcastle, 1976; Hoole, 1999;Mermelstein, 1973;Ö hman, 1967;Perkell, 1969;Stone, 1990͒. The common use of such terms as tip, blade, body, dorsum, and root to refer to the ''parts'' of the tongue reflects the widespread acceptance of this assertion.…”
Section: Introductionmentioning
confidence: 99%
“…There have been relatively few comprehensive reports of across-speaker differences in tongue kinematics largely because the instrumentation for tracking lingual kinematic data is expensive, as are the work hours required for data reduction ͑hence the impetus for the XRMB database; see Westbury, 1994͒. Consequently, most investigations of tongue function have studied seven or fewer participants ͑e.g., Guenther et al, 1999;Harshman et al, 1977;Hoole, 1999;Kent and Moll, 1972;Lofqvist and Gracco, 1994;Perkell and Nelson, 1985;Stone, 1990͒. The few existing investigations that have studied tongue kinematics in a large number of participants have reported large differences across speakers ͑Hashi et Westbury et al, 1998͒.…”
Section: Across-speaker Variationmentioning
confidence: 99%
“…This could occur if a set of observations contains consonant-vowel transitions and rhoticized articulations (cf. Hoole, 1999). It will be shown that even with a small number of observations (between 7 and 13), a reduction to three PCA components is sufficient for statistically meaningful results.…”
Section: A Pca Componentsmentioning
confidence: 99%
“…Multiple regression using PCA components as independent variables is known as principal components regression. Previous studies (Shirai and Honda, 1978;Sekimoto et al, 1978;Maeda, 1978Maeda, , 1990Beaudoin and McGowan, 2000;Story, 2007) have also used PCA and combinations of PCA with other forms of factor analysis (Hoole, 1999) to study midsagittal tongue shape, particularly in vowel production. Shirai and Honda (1978) used 50 vowel tokens from ten different speakers and Sekimoto et al (1978) used over 1000 vowel tokens from two different speakers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation